Online electromechanical modes identification using PMU data - Rios, Mario A.; Ordonez, Camilo A. (2013 IEEE Grenoble PowerTech, 2013)
This paper proposes the identification of electromechanical modes based on signals obtained from Phasor Measurement Unit using a moving time window and a growing window during the post-disturbance state, considering both Prony's method and the Hankel's total least square method. Results show that the two methods can be used for online identification of oscillation modes; however, the moving window must not be shorter than the period of the lowest frequency determined by offline Eigenvalues analysis.